Advantages of treatment of chronic generalized periodontitis with Bepanten ointment containing propolis - Rajabova Dilavfruz Bozorovna (Genius Journals, 2022)
This article discusses the benefits of including propolis-containing ointment in complex therapeutic measures when generalized periodontitis is combined with cardiovascular diseases
Keywords: Periodontitis; tartar; inflammation; bepanten